AMPK and its Activator Berberine in the Treatment of Neurodegenerative Diseases - Qin, Siru; Tang, Huiling; Li, Wei; Gong, Yinan; Li, Shanshan; Huang, Jin; Fang, Yuxin; Yuan, Wenjuan; Liu, Yangyang; Wang, Shenjun; Guo, Yongming; Guo, Yi; et al. (Current Pharmaceutical Design, 2020)
Neurodegenerative disorders are heterogeneous diseases associated with either acute or progressive neurodegeneration, causing the loss of neurons and axons in the central nervous system (CNS), showing high morbidity and mortality, and there are only a few effective therapies. Here, we summarized that the energy sensor adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK), and its agonist berberine can combat the common underlying pathological events of neurodegeneration, including oxidative stress, neuroinflammation, mitochondrial disorder, glutamate excitotoxicity, apoptosis, autophagy disorder, and disruption of neurovascular units. The abovementioned effects of berberine may primarily depend on activating AMPK and its downstream targets, such as the mammalian target of rapamycin (mTOR), sirtuin1 (SIRT1), nuclear factor erythroid-2 related factor-2 (Nrf2), nuclear factor-ΚB (NF-ΚB), phosphoinositide 3-kinase/protein kinase B (PI3K/Akt), nicotinamide adenine dinucleotide (NAD+), and p38 mitogen-activated protein kinase (p38 MAPK). It is hoped that this review will provide a strong basis for further scientific exploration and development of berberine's therapeutic potential against neurodegeneration.
Keywords: oxidative stress